Risk of institutionalization following fragility fractures in older people - Benzinger, Petra; Riem, S.; Bauer, Jürgen M.; Jaensch, Andrea; Becker, C.; Büchele, Gisela; Rapp, Kilian (Osteoporosis international, 2019)
Previously independent living older people suffering fractures of the hip have a high risk of new admission to a nursing home during the subsequent months. This study shows that older people admitted to hospital for fractures of the pelvis and spine have a similar risk of admission to a nursing home.
Gesehen am 17.04.2020